INTERAKSI AKTOR DALAM PERUMUSAN KEBIJAKAN PENGELOLAAN PERTAMBANGAN DI KABUPATEN KOLAKA UTARA - Fahrul Rijal; Muhlis Madani; Fatmawati Fatmawati (Otoritas : Jurnal Ilmu Pemerintahan, 2013)
This study aimed at knowing how the interaction of the actors in policy formulation. The method used was quantitative descriptive supported by qualitative data in the form of frequency tables. 20 people of population in the study would be also as the sample. Techniques of Data Collection in this research would be observation, questionnaires and developed the interviews for the respondent. The data were analyzed quantitative descriptively in which analyzing all the data collected by the authors, and then presented in the form of frequency tabulation completed by responds of the respondents obtained from informants, interviews, and questionnaires. The results showed how the interaction of actors in policy formulation mining management by the following indicators: 1. Patterns of cooperation (bargaining), The relationship between Parliament and Local Government established and done well and successfully, 2. Persuasive models (persuasion), a). An accurate negotiation precision, b). Many of them had been agreed of the approval for the local government and parliament in compromising problems occurred. The factors that influence were supporting factors and inhibiting factors. The supporting factors of the actors interaction and formulation of mining management policy in North Kolaka were: a). communication. b). Actors human resources. Factors inhibiting the interaction of actors in the formulation of management policies of mining management northern Kolaka. a). Commitment. b). Bureaucratic structure.   Penelitian ini bertujuan untuk mengetahui bagaimana interaksi aktor dalam perumusan kebijakan. Metode penelitian yang digunakan adalah deskriptif kuantitatif yang didukung dengan data kualitatif dalam bentuk tabel frekuensi. Populasi dalam penelitian sekaligus merupakan sampel sebanyak 20 orang. Data dikumpulkan dengan menggunakan teknik berupa observasi, kuesioner serta dikembangkan dengan wawancara kepada responden. Data tersebut dianalisis secara Deskriptip kuantitatif yaitu menganalisis semua data yang berhasil dikumpulkan penulis, dan selanjutnya disajikan dalam bentuk tabulasi frekuensi dilengkapi dengan tanggapan responden yang diperoleh dari hasil Informan, wawancara, dan kuesioner. Dari hasil penelitian menunjukkan bagaimana interaksi aktor dalam perumusan kebijakan pengelolaan pertambangan dengan indikator: 1. Pola kerja sama (bar- gaining), Hubungan yang terjalin antara DPRD dan Pemerintah Daerah terjalin baik dan berhasil dilakukan, 2. Model persuasif (persuasion), a). ketepatan negosiasi tepat, b). persetujuan pemerintah daerah dan DPRD dalam mengkompromikan permasalahan yang terjadi banyak yang setuju. Faktor- faktor yang mempengaruhi seperti faktor pendukung dan faktor penghambat. Adapun faktor pendukung interaksi aktor dam perumusan kebijakan pengelolaan pertambangan di Kabupaten Kolaka Utara ialah: a). komunikasi. b). sumber daya pelaksana. Faktor penghambat interaksi aktor dalam perumusan kebijakan pengelolaan pertambangan di kabupaten kolaka utara. a). Komitmen. b). Struktur birokrasi.